Effect of thoracic paravertebral nerve block on delirium in patients after video-assisted thoracoscopic surgery: a systematic review and meta-analysis of randomized controlled trials - Zhou, Xuelei; Mao, Wei; Zhao, Li; Zhu, Hongyu; Chen, Linlin; Xie, Ying; Li, Linji (Frontiers in Neurology, 2024)
Nerve blocks are widely used in various surgeries to alleviate postoperative pain and promote recovery. However, the impact of nerve block on delirium remains contentious. This study aims to systematically evaluate the influence of Thoracic Paravertebral Nerve Block (TPVB) on the incidence of delirium in patients post Video-Assisted Thoracoscopic Surgery (VATS).We conducted a systematic search of PubMed, Embase, Web of Science, Cochrane Library, and Scopus databases in June 2023. The search strategy combined free-text and Medical Subject Headings (MeSH) terms, including perioperative cognitive dysfunction, delirium, postoperative cognitive dysfunction, paravertebral nerve block, thoracic surgery, lung surgery, pulmonary surgery, and esophageal/esophagus surgery. We utilized a random effects model for the analysis and synthesis of effect sizes.We included a total of 9 RCTs involving 1123 participants in our study. In VATS, TPVB significantly reduced the incidence of delirium on postoperative day three (log(OR): -0.62, 95% CI [-1.05, -0.18], p = 0.01, I² = 0.00%) and postoperative day seven (log(OR): -0.94, 95% CI [-1.39, -0.49], p < 0.001, I² = 0.00%).Additionally, our study indicates the effectiveness of TPVB in postoperative pain relief (g: -0.82, 95% CI [-1.15, -0.49], p < 0.001, I² = 72.60%). The comprehensive results suggest that in patients undergoing VATS, TPVB significantly reduces the incidence of delirium and notably diminishes pain scores.